HOW THE BRAIN LEARNS NEW WORDS: VOCABULARY ACQUISITION - Mohichehra Rustamjonova Jahongir qizi (Bright Mind Publishing, 2025)
This article explores the process of vocabulary acquisition, its connection to the brain, common challenges that learners encounter, effective strategies for memorization and retention, and practical implications for both students and teachers.
Keywords: Vocabulary Acquisition, hippocampus, prefrontal cortex, declarative memory, spaced repetition, active engagement, long-term memory, short-term memory.